Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.4414/smw.2022.w30183
|View full text |Cite
|
Sign up to set email alerts
|

Critical care staffing ratio and outcome of COVID-19 patients requiring intensive care unit admission during the first pandemic wave: a retrospective analysis across Switzerland from the RISC-19-ICU observational cohort

Abstract: STUDY AIM: The surge of admissions due to severe COVID-19 increased the patients-to-critical care staffing ratio within the ICUs. We investigated whether the daily level of staffing was associated with an increased risk of ICU mortality (primary endpoint), length of stay (LOS), mechanical ventilation and the evolution of disease (secondary endpoints). METHODS: We employed a retrospective multicentre analysis of the international Risk Stratification in COVID-19 patients in the ICU (RISC-19-ICU) registry, limite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…It is also worth noting that some studies found no difference in mortality among patients with COVID-19 during surge months or based on resource availability ( 171 ). However, it is possible that hospitals worldwide experienced a surge of patients with COVID-19 during different time frames based on spread of the culprit virus, and this variation in timing was a confounding factor in applied analyses.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that some studies found no difference in mortality among patients with COVID-19 during surge months or based on resource availability ( 171 ). However, it is possible that hospitals worldwide experienced a surge of patients with COVID-19 during different time frames based on spread of the culprit virus, and this variation in timing was a confounding factor in applied analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we employed the occupancy ratio on the day of ICU admission as an indicator of the ICU's strain level. Nevertheless, a more exact delineation of "strain" would be advantageous, given the current disparity in definitions across studies (27,(33)(34)(35)(36)(37)(38). Disparities in definition may, to some extent, account for variations in the observed effect sizes regarding strain's impact on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Surge was associated with higher mortality in 32 of 39 studies (82%), including 26 of 31 COVID-19 studies (84%), 4 of 6 non-COVID-19 studies (67%), and 2 of 2 studies that included patients with and without COVID-19. Notably, seven studies (18%) (one using composite metric, three using occupancy, and the remaining three using indirect caseload metrics) reported no impact on mortality with caseload surge (eTable 5, http://links.lww.com/CCM/H520) (6,17,18,37,38,47,35). Only one (25%) of four studies using indirect caseload metrics reported worse survival with surge (42).…”
Section: Surge-mortality Relationship Across Caseload-based Studiesmentioning
confidence: 99%
“…), care settings (emergency departments, hospitals, ICUs), and global regions with differing baseline healthcare infrastructure using a variety of traditional and novel exposures and surge metrics. Results have been inconsistent, some demonstrated surge-associated harm (3)(4)(5), while others showed no effect (6,7), and a few even demonstrated better outcomes (8,9) at surging hospitals. Furthermore, no studies have systematically summarized the evidence addressing this question.…”
mentioning
confidence: 99%